Multi-omic Directed Networks Describe Features of Gene Regulation in Aged Brains and Expand the Set of Genes Driving Cognitive Decline - Tasaki, Shinya; Gaiteri, Chris; Mostafavi, Sara; Yu, Lei; Wang, Yanling; De Jager, Philip L.; Bennett, David A. (Frontiers in Genetics, 2018)
Multiple aspects of molecular regulation, including genetics, epigenetics, and mRNA collectively influence the development of age-related neurologic diseases. Therefore, with the ultimate goal of understanding molecular systems associated with cognitive decline, we infer directed interactions among regulatory elements in the local regulatory vicinity of individual genes based on brain multi-omics data from 413 individuals. These local regulatory networks (LRNs) capture the influences of genetics and epigenetics on gene expression in older adults. LRNs were confirmed through correspondence to known transcription biophysics. To relate LRNs to age-related neurologic diseases, we then incorporate common neuropathologies and measures of cognitive decline into this framework. This step identifies a specific set of largely neuronal genes, such as STAU1 and SEMA3F, predicted to control cognitive decline in older adults. These predictions are validated in separate cohorts by comparison to genetic associations for general cognition. LRNs are shared through www.molecular.network on the Rush Alzheimer’s Disease Center Resource Sharing Hub (www.radc.rush.edu).